COVID-19-Induced Mesenteric Thrombosis - Hanif, Muhammad (Cureus, 2021)
Gastrointestinal symptoms, such as diarrhea (most common among gastrointestinal symptoms), nausea/vomiting, anorexia, abdominal pain, abnormal liver enzymes, and pancreatitis, are being increasingly recognized in patients with coronavirus disease 2019 (COVID-19). Moreover, COVID-19 has also been implicated in coagulopathy, especially in patients with severe disease. Here, we report a case of acute intestinal ischemia secondary to superior mesenteric thrombosis in a young female patient with mild COVID-19.